Unexpected curious cause of serious air leakage after endotracheal intubation: A case report of tracheobronchomegaly and literature review - Xiong, Jun; Zhou, Quan; Li, Yu; Sun, Yanyan; Zhang, Yajun (Frontiers in Surgery, 2022)
Purpose Tracheobronchomegaly (TBM) is a rare disease with enlarged trachea and mainstem bronchi, which might not be diagnosed preoperatively because of patient’s non-symptoms or clinician’s overlook. These patients would be in fatal risk after general anesthesia endotracheal intubation due to severe peritubal leakage. This case may provide helpful and informative resource for anesthesiologists and other clinicians, especially those managing patients’ airway. Clinical feature We presented a patient undergoing elective scoliosis orthopedics was postoperatively diagnosed with tracheobronchomegaly. After general anesthesia endotracheal intubation, difficulty to maintain ventilation with obvious peri-cuff air leakage made this rare disease to be suspected. The peritubal leakage was resolved by relocating endotracheal tube to subglottic area. Fortunately, there were no air leakage and postoperative complications. Conclusion Anesthesiologists should keep the possibility of unpredicted anatomic abnormal respiratory tract in mind, such as tracheobronchomegaly.